Point-of-care ultrasound competency of doctors working in Cape Town emergency departments - Karen Ferreira; Clint Hendrikse; Heinri Zaayman; Elaine Erasmus; Daniël J. van Hoving (South African Family Practice)
Background: Point-of-care ultrasound (PoCUS) is a core competency in emergency medicine, and its use in other primary healthcare settings is growing. The study investigates the PoCUS competency, training and qualifications of doctors working in public emergency departments.